XPS Studies of Electrodeposited Grown F-Doped ZnO Rods and Electrical Properties of p-Si/n-FZN Heterojunctions. (15th June 2016) - Ilican, Saliha; Caglar, Mujdat; Aksoy, Seval; Caglar, Yasemin
Abstract : The chemical composition of the electrodeposited undoped and F-doped ZnO (FZN) rods was investigated by X-ray photoelectron spectroscopy (XPS). These results confirmed the existence of F as a doping element into ZnO crystal lattice. The p-Si/n-ZnO and p-Si/n-FZN heterojunction diodes were fabricated and their electrical properties were investigated. Some parameters belong to these diodes such as ideality factor ( n ), barrier height (ϕ B ), and series resistance (R s ) which were calculated from the current-voltage ( I-V ) curves that exhibited rectifying behavior by using thermionic emission theory, Norde's function, and Cheung's method. There is a good agreement between the diode parameters obtained from different methods.